2017
DOI: 10.3168/jds.2016-11976
|View full text |Cite
|
Sign up to set email alerts
|

Finances and returns for robotic dairies

Abstract: Automatic milking systems (AMS) became commercially available in the early 1990s. These systems provide flexibility and improve the lifestyle of farmers installing them. Because of the larger capital cost per kilogram of milk produced, observational studies in Europe and simulation studies have shown AMS to be less profitable than milking parlor systems, although previous findings are somewhat mixed. Improved performance of newer generations of AMS, better facility design to accommodate cow behavior, and bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 13 publications
(35 reference statements)
3
17
0
1
Order By: Relevance
“…Also, the currently presented results in this respect were similar to those obtained in previous studies (Waśkowicz et al, 2014;Piwczyński et al, 2020a). Salfer et al (2017) noted yet another important benefit for AMS farms, namely pelleted feed supplementation in AMS box was strongly associated with body condition and thus might cause the increase in milk production. When analysing the rumination activity of cows (measured by the number of minutes per day), it was found that rumination time was the shortest in the US (468.99 minutes), and the longest in the LV (504.86 minutes) (Table 4).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Also, the currently presented results in this respect were similar to those obtained in previous studies (Waśkowicz et al, 2014;Piwczyński et al, 2020a). Salfer et al (2017) noted yet another important benefit for AMS farms, namely pelleted feed supplementation in AMS box was strongly associated with body condition and thus might cause the increase in milk production. When analysing the rumination activity of cows (measured by the number of minutes per day), it was found that rumination time was the shortest in the US (468.99 minutes), and the longest in the LV (504.86 minutes) (Table 4).…”
Section: Resultssupporting
confidence: 90%
“…Castro et al (2012) found that varying number of cows per robot and the milk speed had the greatest effect on the daily milk yield in AMS. Salfer et al (2017) emphasised that management system in AMS equipped barns should be properly parameterized in such a way that it makes sure that cows occupy robots at the right time. In AMS, the amount of milk obtained by the robot per day is of key importance in shaping the profitability of production, which is directly related to the amount of milk collected per minute of the time cow spends in the milking stall -milk efficiency (kg/min).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As higher milking frequency increase milk production, an important question is how to make cows access the AMS more often. Salfer, Minegishi, Lazarus, Berning and Endres (2017) reported that AMS management system should be properly parameterized so that the right cow could occupy the AMS at the right time. Early lactating cows, which theoretically seek more the AMS during the day, should have a greater number of permissions to access the equipment and be milked.…”
Section: Increase In Milk Yieldmentioning
confidence: 99%
“…Automatic milking systems (AMS) became commercially available in the early 1990 [1]. Opinions on this new milking technology vary among farmers, experts and researchers [2].…”
Section: Introductionmentioning
confidence: 99%